The sound construction in "Estorvo" (1991) by Chico Buarque - Morales, Hernán (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
On the basis of Chico Buarque’s poetry regarding one of his novels, Estorvo (1991), we set out to investigate aspects that would place this musician/writer’s stories between the sonorous and the verbal. A narrative where conventional traits crack by a decentering that compromises the "meeting" of languages, records, speeches, figurations, sonorities in the space of Latin American settings. Such encounters would create as a contact area, a single grammar hybridized discourse, displaced from known patterns, among others, in order to configure infrequent tensions in narrative texts (Literature/Music, word/sound).